The Oxford guide to United States Supreme Court decisions - Hall, Kermit L., 1944-2006.; Ely, James W., 1938-; Oxford eBooks ([New York] : Oxford University Press, 2009)
Here are the landmark decisions that have shaped American life, described by some of America's most eminent legal scholars. The new edition contains more than 450 entries on major cases, including 53 new entries on the latest landmark rulings. This outstanding guide serves as an excellent introduction to the work of the Court from the late eighteenth century to the present day.
"Oxford Reference Online Premium."
Title from home page (viewed Jan. 5, 2010).
Also issued in print format.
Keywords: Constitutional law -- United States -- Encyclopedias; Constitutional law -- United States -- Digests; Electronic books